Clinical practice pattern on hematuria and proteinuria in children: the report of a survey for the Korean Society of Pediatric Nephrology - Jeesu Min; Naye Choi; Yo Han Ahn; Hee Gyung Kang (Korean Society of Pediatric Nephrology, 2023)
Purpose Hematuria and proteinuria have various causes and consequential outcomes in children. Immunosuppressants are needed in some children with biopsy-proven glomerulonephropathy but have many adverse effects. Since the clinical practice patterns of Korean pediatric nephrologists are diverse, we surveyed their opinions. Methods Using a clinical vignette, the survey was emailed to all Korean Society of Pediatric Nephrology members. The questionnaires included diagnosis, examination, medications, and dietary recommendations for patients with hematuria and proteinuria. Results A total of 32 clinicians (5.48%, 22 pediatric certificated nephrologists) responded to the survey. Most responders (87.5%) suspected immunoglobulin A nephropathy, and 68.8% replied that kidney biopsies were a diagnostic tool. Renin-angiotensin system inhibition (62.5%) or steroids (18.8%) were selected as the treatment. Salt and protein intakes were usually encouraged as dietary reference intakes (34.4% and 65.6%, respectively). Conclusions Children with abnormal urinalysis have various causes, treatments, and prognoses. As treatments such as immunosuppressants can have many adverse effects, it is necessary to confirm an accurate diagnosis and indications of treatments before starting the treatment. Recommendations for a diet should not hinder growth.